Quartz-Tuning-Fork-Enhanced Spectroscopy Based on Fast Fourier Transform Algorithm - Yang, Guangxiang; Xu, Linguang; Liang, Hua; Li, Jingsong (Frontiers in Physics, 2020)
In this paper, a gas sensing technique based on quartz-crystal-tuning-fork enhanced spectroscopy (QCTFES) and wavelength modulation spectroscopy (WMS) is reported. To explore the capabilities of this technique, detection of trace methane (CH4) was demonstrated using a near infrared distributed feedback diode laser near 1.653 μm and a single pass gas absorption cell with an optical length of 20 cm. For signal processing, a fast and effective signal analysis method based on Fast Fourier transform (FFT) algorithm is proposed for extracting the absorption intensity signal of the QCTFES-WMS, instead of a lock-in amplifier used for harmonic signal demodulation in traditional QCTF based detection techniques. Primary laboratory results indicate that an excellent linearity response of CH4 concentration and optical power levels are founded, and a detection limit of 64 ppm is achieved for a 1s averaging time, which can be further improved to 9 ppm with an averaging time of 250 s. Improvements in sensitivity and detectivity can be significantly improved if a higher power laser source is available. Compared to traditional WMS technique based semiconductor photodetectors, the room-temperature QCTF-based WMS shows significant advantages of super-broadband wavelength response, much cheap and tiny.